Adipose Stromal Cells Repair Pressure Ulcers in Both Young and Elderly Mice: Potential Role of Adipogenesis in Skin Repair. (21st April 2015) - Strong, Amy L.; Bowles, Annie C.; MacCrimmon, Connor P.; Frazier, Trivia P.; Lee, Stephen J.; Wu, Xiying; Katz, Adam J.; Gawronska-Kozak, Barbara; Bunnell, Bruce A.; Gimble, Jeffrey M.
Abstract : This study uses a murine model to address the hypothesis that adipose-derived stromal/stem cell (ASC) treatment would accelerate and enhance pressure ulcer repair. The results are consistent with clinical reports that fat grafting improved skin architecture in thermal injuries, thus setting the stage for clinical translation of autologous and/or allogeneic ASC treatment of pressure ulcers. Abstract: : More than 2.5 million patients in the U.S. require treatment for pressure ulcers annually, and the elderly are at particularly high risk for pressure ulcer development. Current therapy for pressure ulcers consists of conservative medical management for shallow lesions and aggressive debridement and surgery for deeper lesions. The current study uses a murine model to address the hypothesis that adipose-derived stromal/stem cell (ASC) treatment would accelerate and enhance pressure ulcer repair. The dorsal skin of both young (2 months old [mo]) and old (20 mo) C57BL/6J female mice was sandwiched between external magnets for 12 hours over 2 consecutive days to initiate a pressure ulcer. One day following the induction, mice were injected with ASCs isolated from congenic mice transgenic for the green fluorescent protein under a ubiquitous promoter. Relative to phosphate-buffered saline-treated controls, ASC-treated mice displayed a cell concentration-dependent acceleration of wound closure, improved epidermal/dermal architecture, increased adipogenesis, and reduced inflammatory cell infiltration. The ASC-induced improvements occurred in both young and elderly recipients, although the expression profile of angiogenic, immunomodulatory, and reparative mRNAs differed as a function of age. The results are consistent with clinical reports that fat grafting improved skin architecture in thermal injuries; the authors of this published study have invoked ASC-based mechanisms to account for their clinical outcomes. Thus, the current proof-of-principle study sets the stage for clinical translation of autologous and/or allogeneic ASC treatment of pressure ulcers. Significance: Adipose-derived stromal/stem cells (ASCs) promote the healing of pressure ulcer wounds in both young and old mice. ASCs enhance wound healing rates through adipogenic differentiation and regeneration of the underlying architecture of the skin.